Case Report: Neurodegenerative Diseases After Severe Acute Respiratory Syndrome Coronavirus 2 Infection, a Report of Three Cases: Creutzfeldt–Jakob Disease, Rapidly Progressive Alzheimer's Disease, and Frontotemporal Dementia - Pimentel, Gabriela Almeida; Guimarães, Thiago Gonçalves; Silva, Guilherme Diogo; Scaff, Milberto (Frontiers in Neurology, 2022)
The relationship of SARS-CoV-2 and neurodegenerative diseases is yet to be fully clarified. Fast worsening and even new onset cases of those disorders have been reported in association with COVID-19. In this series, we describe three cases of neurodegenerative diseases in patients with SARS-CoV-2: a case of Creutzfeldt-Jakob disease during COVID-19 acute phase, to our knowledge the second one described in the literature; a rapidly progressive Alzheimer´s Disease; and a patient with frontotemporal dementia and a quick decline of both cognitive and behavioral domains. This report aims at drawing neurologist´s attention to the possibility of an association between SARS-CoV-2 and a higher probability of developing or accelerating neurodegenerative chronic neurologic conditions, and reinforce the need for a close cognitive follow-up after the infection is resolved.